Religious Education at Schools in Republic of North Macedonia - Aneta Jovkovska; Zlateski, Petko (V&R unipress, 2020)
The Republic of North Macedonia is a secular country with a separation of church and state. The churches and religious communities in North Macedonia have the right to found religious educational institutions on all levels of education, except for the elementary level, for the education of clergy and other personnel. Hence, the two most common religions in North Macedonia: Orthodox Christianity and Islam have their own educational institutions in middle and higher education with old traditions and many years of experience. In public education, religious education is found only in elementary education, where the subject Ethics in religions is learned as an optional subject in sixth grade. According to the curriculum this subject has the purpose of developing a sense of responsibility, the capacity to tell good from evil, prudence, to understand the significance of spiritual and material, respect toward religious wealth, religious traditions and religious differences in the world, as well as of increasing the children’s personal integrity and dignity.